Identification of the Dynamic Characteristics of Luffa Fiber Reinforced Bio-Composite Plates - GENÇ, GARİP (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2017)
Luffa cylindrica plant fiber is a new biodegradable engineering material. However, the dynamic behaviors of these new green materials or their composites should be explored to consider them for practical applications. The dynamic characteristics including modal behavior and the elastic and sound isolation properties of luffa-based bio-composite plates were explored in this study. Structural frequency response function measurements were conducted using a few luffa bio-composite plates to identify their modal behavior. The modal frequencies and loss factors of the luffa bio-composite plates were identified by analyzing the frequency response function measurements using a few modal analysis methods such as half-power, circle-fit, and line-fit. The same luffa bio-composite structures were modelled using a finite element formulation with damping capability, and the elastic moduli of the composite plates were identified. In addition, the transmission loss levels of the same luffa composite samples were measured using the impedance tube method. The results showed that luffa composite structures have considerably high stiffness (elasticity modulus: 2.5 GPa), damping levels (loss factor: 2.6%), and transmission loss level (25 to 30 dB for a 1 cm thickness), and their mechanical properties are promising as an alternative disposable material for noise and vibration control engineering applications.
Keywords: Bio-composites; Luffa Composites; Elastic Properties; Damping Levels; Transmission Loss; FEM Modeling; MECHANICAL-PROPERTIES; CYLINDRICA FIBERS; DAMPING CAPABILITY; SPONGE; BEHAVIOR; SOUND; POLYESTER; ELEMENT